Efektifitas Mendengarkan Musik Saat Jogging Terhadap Mood Mahasiswa Olahraga - Tasya Fatimah; Herman Subarjah; Mohammad Zaky (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The aim of this research is to examine the impact of listening to music while jogging. The method used in this research is a Causal Comparative research design. Where the sample population in this study was sports students, totaling 100 people and divided into two groups, namely a group that was given treatment and one group that did not receive treatment and functioned as a control or comparison group. The mood instrument used is The Brunnel Mood Scale (BRUMS) developed by Peter C Terry (2010). From the results of the Independent sample t-test, the resulting p-value is 0.00, this value is smaller than the significance level of 0.05, which means there is a significant difference between the Mood value of listening to music and those who don't listen to music.